1999
DOI: 10.1034/j.1399-3054.1999.105225.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate reductase in higher plants: A case study for transduction of environmental stimuli into control of catalytic activity

Abstract: In higher plants, cytosolic NAD(P)H‐nitrate reductase (NR) is rapidly modulated by environmental conditions such as light, CO2, or oxygen availability. In leaves, NR is activated by photosynthesis, reaching an activation state of 60–80%. In the dark, or after stomatal closure, leaf NR is inactivated down to 20 or 40% of its maximum activity. In roots, hypoxia or anoxia activate NR, whereas high oxygen supply inactivates NR. Spinach leaf NR is inactivated by phosphorylation of serine 543 and subsequent Mg2+‐dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(124 citation statements)
references
References 57 publications
3
114
0
7
Order By: Relevance
“…It seems that the carbon sources effective in reactivation of NR must enter the carbohydrate metabolism and be able to replenish the hexose pools (Fig. 3) or to increase the content of sugar phosphates, which are known to protect NR against dark inactivation (De Cires et al, 1993) most probably due to the inactivation of the NR protein kinase (Kaiser et al, 1999). Not all carbon sources were able to restore NR activity after the treatment in air without CO 2 , as demonstrated by lack of effect after addition of OAS (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the carbon sources effective in reactivation of NR must enter the carbohydrate metabolism and be able to replenish the hexose pools (Fig. 3) or to increase the content of sugar phosphates, which are known to protect NR against dark inactivation (De Cires et al, 1993) most probably due to the inactivation of the NR protein kinase (Kaiser et al, 1999). Not all carbon sources were able to restore NR activity after the treatment in air without CO 2 , as demonstrated by lack of effect after addition of OAS (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…One component, in particular nitrate assimilation, is a major sink for reductant in the light (Bloom et al 1989), and nitrate reductase activity is strongly enhanced by light both at the transcriptional and translational levels (Kaiser, Weiner & Huber 1999;Sherameti et al 2002;Stitt et al 2002). Nitrogen assimilation is also suppressed by a reduction in carbohydrate status (Fritz et al 2006), and therefore by the duration of the dark period.…”
Section: The Role Of Variation In Anabolic Demandsmentioning
confidence: 99%
“…NR seems to play a role similar to the D 1 protein. Recent studies have indicated that NR is highly regulated by complex transcriptional and posttranslational mechanisms (Campbell 1999;Huber et al 1996;Kaiser et al 1999). The NR enzyme is degraded after several hours in the dark (Kelker & Filner 1971).…”
Section: Perspectivesmentioning
confidence: 99%